The Harmful Use of Isolation in Juvenile Facilities: The Need for Post-Disposition Representation - Sandra Simkins; Marty Beyer; Lisa M. Geis (Washington University Journal of Law & Policy, 2012)
Part I of this Article describes the components of our post-disposition project, including an outline of the legal parameters of New Jersey juvenile law as it relates to post-disposition representation. Part II addresses the issue of isolation in juvenile facilities. This section looks at the current definition of isolation and available research concerning the harmful effects that isolation has on the juvenile population, featuring the work of clinical psychologist Dr. Marty Beyer. It also reviews the judicial response to the use of isolation in juvenile facilities and examines how isolation is used in New Jersey facilities and the legal structure that permits this. Part II concludes with a review of the national standards of juvenile isolation, and highlights the various investigations conducted across the country. Part III uses In Re O.S. to illustrate the problems we found in New Jersey‘s secure juvenile facilities and the challenges we faced when trying to use the existing New Jersey structure to address those problems. Part IV first shows that isolation does not have the purported benefits of safety, punishment, or deterrence in juvenile facilities, demonstrates that juvenile facilities can manage youth more effectively with treatment instead of isolation, and proposes strategies for the future and suggests how the juvenile defender community might respond.
Keywords: Juvenile detention homes; Recidivism; Solitary confinement; United States